Improving critical care through telemedicine: a comprehensive analysis of a Tele-ICU project in northern and northeastern regions of Brazil - Shoraya Virginio Carneiro Dal Col; Eduardo Leite Vieira Costa; Diego Britto Ribeiro; Thalyta Flores; Franca Pellison; Larissa Borges Moraes; Ana Luiza Inglesi Arevalo; Anna Carolina Pompermayer Coradelli; Elen Moda de Oliveira Azevedo; Isadora Stefanini Guimarães; Katia Dione da Gama; Rafaella Coutinho Grecco Aguiar; et al. (BMC Health Services Research)
Abstract Introduction The Tele-Intensive Care Unit (Tele-ICU) project aimed to standardize and improve the quality of critical care services, particularly in regions where access to specialized care and resources remains limited. We herein provide a detailed overview of the implementation of the Tele-ICU project in Brazil’s northern and northeastern regions, describing its multi-modal approach, which combined telemedicine implementation, educational initiatives, simulation-based training, protocol development, and structured data reporting to enhance critical care delivery. Methods The implementation of the Tele-ICU project, developed in a partnership between the Ministry of Health and Hospital Sírio-Libanês from June 2022 to December 2023, was supported by the Support Program for Institutional Development of the Unified Health System (PROADI-SUS). The intervention strategy included on-site implementation workshops, tele-rounds, and structured educational initiatives. A set of indicators was collected to monitor the implementation process. A mixed-methods approach was employed to analyze quantitative indicators and qualitative feedback from intensive care unit (ICU) teams. Results A total of 5,471 patients were treated across 15 ICUs through 3,971 tele-rounds. During these tele-rounds, 20,168 telehealth visits—bedside discussions focused on individual patients—were conducted, covering 74% of inpatients. Additionally, 30 educational activities were developed, involving 760 health professionals. Participants reported high levels of satisfaction throughout the project. Conclusion This study demonstrated the feasibility of implementing telemedicine in critical care delivery within resource-limited settings. Our findings suggest that the Tele-ICU model can be a scalable solution for enhancing critical care in these environments.